Effects of naturally-produced lovastatin on feed digestibility, rumen fermentation, microbiota and methane emissions in goats over a 12-week treatment period - Su Chui Len Candyrine; Mazrul Fahmi Mahadzir; Sani Garba; Mohammad Faseleh Jahromi; Mahdi Ebrahimi; Yong, Meng Goh; Anjas Asmara Samsudin; Awis Qurni Sazili; Wei, Li Chen; Siva Ganesh; Ron Ronimus; Stefan Muetzel; et al. (2018)
Twenty male Saanen goats were randomly assigned to four levels of lovastatin supplementation and used to determine the optimal dosage and sustainability of naturally produced lovastatin from fermentation of palm kernel cake (PKC) with Aspergillus terreus on enteric methane (CH4) mitigation. The effects on ruminal microbiota, rumen fermentation, feed digestibility and health of animal were determined over three measuring periods (4-, 8- and 12-weeks) and the accumulation of lovastatin in tissues was determined at the end of the experiment. The diets contained 50% rice straw, 22.8% concentrates and 27.2% of various proportions of untreated or treated PKC to achieve the target daily intake level of 0 (Control), 2, 4 or 6 mg lovastatin/kg body weight (BW). Enteric CH4 emissions per dry matter intake (DMI), decreased significantly (P<0.05) and equivalent to 11% and 20.4%, respectively, forthe 2 and 4 mg/kg BW groups as compared to the Control. No further decrease in CH4 emission thereafter with higher lovastatin supplementation. Lovastatin had no effect on feed digestibility and minor effect on rumen microbiota, and specifically did not reduce the populations of total methanogens and Methanobacteriales (responsible for CH4 production). Similarly, lovastatin had little effect on rumen fermentation characteristics except that the proportion of propionate increased, which led to a decreasing trend (P<0.08) in acetic: propionate ratio with increasing dosage of lovastatin. This suggests a shift in rumen fermentation pathway to favor propionate production which serves as H+ sink, partly explaining the observed CH4 reduction. No adverse physiological effects were noted in the animals except that treated PKC (containing lovastatin) was less palatable at the highest inclusion level. Lovastatin residues were detected in tissues of goats fed 6 mg lovastatin/kg BW at between 0.01 to 0.03 μg/g, which are very low.